EAFF Call to Action for COP28 - Eastern Africa Famers Federation (2023)
The Eastern Africa Farmer’s Federation (EAFF), which comprises of 24 farmer organisations from 10 countries, has signed a shared call-to-action to enhance the role of farmers in climate policy and within the international climate negotiations. The EAFF’s members farmer associations, co-operatives and commodity associations, representing over 25 million farmers across East Africa. Despite the unique national priorities and processes within each member country, this statement serves as a common request for support to enhance farmer-led climate change adaptation and intervention processes at the national and regional level. This collective statement includes key messages from farmer organisations, as well as contributions from the EAFF Secretariat in support of their members.